A Systematic Literature Review of the Burden of Respiratory Syncytial Virus and Health Care Utilization Among United States Infants Younger Than 1 Year . (15th August 2022) - Suh, Mina; Movva, Naimisha; Bylsma, Lauren C; Fryzek, Jon P; Nelson, Christopher B
Abstract: Background: The burden and health care utilization (HCU) of respiratory syncytial virus (RSV) in US infants aged <1 year across health care settings are not well characterized. Methods: We systematically reviewed studies of RSV and bronchiolitis published 2000–2021 (data years, 1979–2020). Outcomes included RSV hospitalization (RSVH)/bronchiolitis hospitalization rates, emergency department (ED)/outpatient (OP) visit rates, and intensive care unit (ICU) admissions or mechanical ventilation (MV) use among RSV-/bronchiolitis-hospitalized infants. Study quality was determined using standard tools. Results: We identified 141 good-/fair-quality studies. Five national studies reported annual average RSVH rates (range, 11.6 per 1000 per year among infants aged 6–11 months in 2006 to 50.1 per 1000 per year among infants aged 0–2 months in 1997). Two national studies provided RSVH rates by primary diagnosis for the entire study period (range, 22.0–22.7 per 1000 in 1997–1999 and 1997–2000, respectively). No national ED/OP data were available. Among 11 nonnational studies, RSVH rates varied due to differences in time, populations (eg, prematurity), and locations. One national study reported that RSVH infants with high-risk comorbidities had 5-times more MV use compared to non–high-risk infants in 1997-2012. Conclusions: Substantial data variability was observed. Nationally representative studies are needed to elucidate RSV burden and HCU.